2020
DOI: 10.1016/j.bpj.2020.05.033
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of (−)-Epigallocatechin-3-Gallate on the Amyloid-β Secondary Structure

Abstract: Amyloid-b (Ab) is a macromolecular structure of great interest because its misfolding and aggregation, along with changes in the secondary structure, have been correlated with its toxicity in various neurodegenerative diseases. Small drug-like molecules can modulate the amyloid secondary structure and therefore have raised significant interest in applications to active and passive therapies targeting amyloids. In this study, we investigate the interactions of epigallocatechin-3-gallate (EGCG), found in green t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 67 publications
3
25
0
Order By: Relevance
“…However, further investigation is needed to confirm this assumption. Specifically, mounting evidence has shown that EGCG inhibits the oligomerization of Aβ42 [ 41 , 42 , 43 ]. Consistent with previous work [ 21 ], we found that EGCG induces highly stable aggregates of synthetic Aβ42.…”
Section: Discussionmentioning
confidence: 99%
“…However, further investigation is needed to confirm this assumption. Specifically, mounting evidence has shown that EGCG inhibits the oligomerization of Aβ42 [ 41 , 42 , 43 ]. Consistent with previous work [ 21 ], we found that EGCG induces highly stable aggregates of synthetic Aβ42.…”
Section: Discussionmentioning
confidence: 99%
“…This same lysine also interacted with the gallic acid of EGCG, confirming that group’s critical role in protofibril disruption ( Zhan et al, 2020 ). Thus, it was observed that the central interference promoted by EGCG in fibril formation is the disruption of inter-chain hydrogen bonds and salt bridges crucial to amyloid structure ( Acharya et al, 2020 ). Even though the mechanism of action of EGCG has not been elucidated, the knowledge of some forms of interaction between the compound and amyloid proteins can generate valuable information for therapeutic strategies against aggregation.…”
Section: History Of the Inhibitory Effects Of Epigallocatechin-gallate In Protein Aggregation And Its Use In Neurodegenerative Amyloid DImentioning
confidence: 99%
“…The aromatic rings, hydroxyls groups and gallate motif of EGCG appear to be essential for the interactions with proteins and the anti-amyloid effectiveness ( Rambold et al, 2008 ; Sironi et al, 2014 ; Fusco et al, 2018 ). Moreover, the hydrophobic interactions and hydrogen bonds represent the main form of protein-compound interaction, resulting in inhibition of the conversion in β amyloid toxic structures ( Wang et al, 2010 ), and the break of saline bridges promoted by EGCG can be crucial to interrupt the fibril structuration ( Acharya et al, 2020 ; Yao et al, 2020 ; Zhan et al, 2020 ).…”
Section: History Of the Inhibitory Effects Of Epigallocatechin-gallate In Protein Aggregation And Its Use In Neurodegenerative Amyloid DImentioning
confidence: 99%
“…[55][56][57][58] Abeta being polymorphic in nature each of the bril structure have its own importance and which have been highlighted in the recent experimental and computational studies. [59][60][61][62][63] Also, studies by Cheon M et al 62 & Kahler A et al 63 suggest formation of U-shaped brillar structure from potent on-pathway intermediates of the Ab17-42 pentamer and hexamer oligomers (paranuclei). The U-shaped model (2BEG) has been part of most of the previously reported molecular simulation studies.…”
Section: Molecular Dockingmentioning
confidence: 99%